2023
DOI: 10.1186/s13075-023-03070-2
|View full text |Cite
|
Sign up to set email alerts
|

B cell subsets in adult-onset Still’s disease: potential candidates for disease pathogenesis and immunophenotyping

Abstract: Background Adult-onset Still’s disease (AOSD) is a systemic autoinflammatory disorder of unknown etiology. B cells are critical participants in different rheumatic diseases, and their roles in AOSD are rarely investigated. This study aimed to unveil the B cell subset features in AOSD and provide evidence for B cell-based diagnosis and targeted therapies of AOSD. Methods B cell subsets in the peripheral blood of AOSD patients and healthy controls (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It should be noted that IL-1β promotes B-cell activation, proliferation as well as differentiation into plasma cells [39], which may be closely related to high levels of this cytokine in AOSD during increased disease activity. In contrast, Fang et al showed that active AOSD is paralleled with an increased percentage of "naïve" IgD+CD27-B cells, double-negative IgD-CD27-B cells as well as CD20-CD27hi plasmablasts, whereas the "regulatory" B-cell subsets-IgD+CD27+ and CD24hiCD27+-significantly decreased [40].…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that IL-1β promotes B-cell activation, proliferation as well as differentiation into plasma cells [39], which may be closely related to high levels of this cytokine in AOSD during increased disease activity. In contrast, Fang et al showed that active AOSD is paralleled with an increased percentage of "naïve" IgD+CD27-B cells, double-negative IgD-CD27-B cells as well as CD20-CD27hi plasmablasts, whereas the "regulatory" B-cell subsets-IgD+CD27+ and CD24hiCD27+-significantly decreased [40].…”
Section: Discussionmentioning
confidence: 90%